2015
DOI: 10.1007/s00391-015-0928-6
|View full text |Cite
|
Sign up to set email alerts
|

Stress and biological aging

Abstract: It is well accepted that aging is the basis of most degenerative diseases in the elderly. Biological aging is characterized by a gradual accumulation of cellular and molecular defects. An important cause of defects is intense stress, such as oxidative or glycotoxic stress. Genes affecting cellular and organismal longevity are frequently associated with the regulation of cellular anti-oxidative defense and/or with repair functions. Damage, combined with an age-dependent decline in defense and repair systems, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Longevity is a multifactorial condition, affected by environmental and genetic factors, as well as by oxidative and genomic damage. Several hypotheses have been postulated to explain aging and lifespan, which have attracted widespread scientific and public interest ( Brooks-Wilson, 2013 ; Simm and Klotz, 2015 ). The reactive oxygen species (ROS) theory of aging is related to oxidative stress and macromolecule damage.…”
Section: Introductionmentioning
confidence: 99%
“…Longevity is a multifactorial condition, affected by environmental and genetic factors, as well as by oxidative and genomic damage. Several hypotheses have been postulated to explain aging and lifespan, which have attracted widespread scientific and public interest ( Brooks-Wilson, 2013 ; Simm and Klotz, 2015 ). The reactive oxygen species (ROS) theory of aging is related to oxidative stress and macromolecule damage.…”
Section: Introductionmentioning
confidence: 99%
“…Psychological stressors, linked with the genetic and epigenetic modifications, are known as the influential causal events changing the physiology of many organs of the human body (including brain and gut [ 167 ]) and systems (including an immune [ 168 ] and hormonal [ 36 ]). Aging, accompanied by the decline in health, independence, perceptual, cognitive, and decision-making abilities, is closely associated with the negative impacts of typical psychological stress [ 6 , 169 , 170 ]. Indeed, both psychological stress and aging show cumulative impact on most physiological systems [ 171 , 172 , 173 ] involving biological events at the molecular [ 173 ], cellular [ 174 ] and system [ 34 , 41 ] levels.…”
Section: Discussionmentioning
confidence: 99%
“…Aging is a complex biological process that involves various cellular, molecular and structural changes based on several mechanisms . Accumulating studies found that aging of functional cells was detected in the lungs of asthma patients .…”
Section: Discussionmentioning
confidence: 99%
“…Biological aging includes various cellular, molecular and structural changes based on several theories . Although usually age‐related, biological aging can also occur in early life, partially independent of age .…”
Section: Introductionmentioning
confidence: 99%